Peningkatan Kapasitas Pemasaran Digital Bagi UMKM Keripik Singkong Dua Putri - Yulinar, Shalina; Sukmajati, Fida; Novitasari, Novitasari; Febrian, Moh; Nugraha, Alifian (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
This community service program was implemented to improve the digital marketing capacity of the Dua Putri Cassava Chips MSME located in Danci Hamlet, Kemiri Village. The MSME faces various obstacles such as a lack of understanding of digital marketing, the absence of a professional brand label, a limited digital catalog, and suboptimal use of social media such as TikTok and Instagram. The activity methods used included initial observation, outreach, digital identity creation training, product packaging assistance, social media account creation, and digital content creation training. The results of the activity showed a significant increase in the MSME's ability to create content, manage social media, improve packaging, and develop a digital business identity. Thus, this activity makes an important contribution to increasing the competitiveness of MSMEs in the digital marketing era.